Aquaculture industry potential and issues: a case from cage culture system entrepreneurs: suggestions for intensification of aquaculture industry - A. N., Ahmad Faiz; Idris, Khairuddin; Uli, Jegak; Mohamed Shaffril, Hayrol Azril; L. S., Jeffrey (Science Publications, 2010)
Problem statement: Cage culture has become a popular aquaculture system nowadays. In the recent statistics provided by DOF, the cage culture system has generated almost USD 400 m (RM 1.39 b) of income per year. In order to further intensify this economic activity the Ministry of Agriculture and Agro-based Industry (MOA) through the DOF has zoned the aquaculture industry via Aquaculture Industry Zone (ZIA) Programs throughout Malaysia. Cage culture system seems to have the ability to be a catalyst in enhancing the economy level of local people but it is well known that certain problems must be overcome first before the potential can be clearly seen. Thus the main focus of this study is to clarify all the potentials and problems faced by the cage culture system entrepreneurs in running their aquaculture activity. Approach: The research approach for this study was a qualitative case study that provided an in-depth description of potentials and issues in aquaculture industry in the district of Kuala Pahang, Malaysia. Data was gained using a Focus Group Discussion (FGD) among the cage culture system entrepreneurs guided by an interview guide. A total of 10 cage culture entrepreneurs were selected as the FGD members. The questions served as a guide, but allowed respondents freedom and flexibility in their answers. The findings were in descriptive analysis. Results: The cage culture system was found to provide better income that lead to a higher quality of life for the entrepreneurs, positive intangible values existed among the entrepreneurs; experiences have taught them to become self independent. There were problems identified such as no independence in selecting the fingerlings, environmental problems seem to burden them, unstable pellet price, no official agreement between them and the government emphasizing the portion of the river is given to them for running their business and lot of bureaucracies that the entrepreneurs need to face. Conclusion/Recommendations: Based on the results gained, it can be concluded that even though cage culture industry proved to enhance the level of income and quality of life, a number of problems must be overcome first to further enhance their level of income and quality of life. Therefore, it is a need that the related agencies to provide more financial supports help to solve the environmental problems and further develop their administration aspects to reduce issues such as bureaucracy and official agreement.